Pro Telerik ASP.NET and Silverlight Controls Master Telerik Controls for Advanced ASP.NET and Silverlight Projects - Guay Paz, Jose Rolando; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
This book provides a complete guide to implementing Telerik’s range of ASP.NET and Silverlight controls. Telerik controls are invaluable for ASP.NET and Silverlight developers because they provide a vast array of rich controls targeted for the presentation layer of web applications. Telerik offers you solutions for the reports, grids, charts, and text-editing controls that you need but don’t want to build from scratch yourself—the options are endless for increasing the functionality of any of your web solutions.
Introducing ASP.NET and Telerik -- Getting Started With Telerik RadControls -- Input RadControls -- Navigation RadControls -- Date, Time, and Scheduling RadControls -- Data RadControls, Part 1 -- Data RadControls, Part 2 -- Layout RadControls -- Chart and Image RadControls -- Additional RadControls -- RadAjax -- Telerik Extensions for ASP.NET MVC -- RadControls for Silverlight -- Introducing Telerik Reporting -- Telerik OpenAccess ORM.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems